Istihdamu Lu’batil Bahs Anil Ajanib Litanmiyati Istiabatil Mufrodat fii Tadriisi Al Lughah Al arobiyah littalamid As Soft al Khomis Bil Madrasah Al Ibtidaiyyah Al islamiyah Suren Gede Wonosobo - Azizah, Faizatul; Merdikawati, Lulu; Faizun, Ahmad; Muttaqin, Zaenal (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This research aims to: 1) Find out the use of the unfamiliar search game in mastering Arabic vocabulary for class V MI Ma'arif Suren Gede Kertek Wonosobo students; 2) Knowing how to increase mastery of Arabic vocabulary by using the foreign search game for class V MI Ma'arif Suren Gede Kertek Wonosobo students. This type of research is field research (al-bahtsu al-maidaniy) where researchers collect data directly at the research location using observation, interviews, documentation and tests. The approach taken by researchers in this research is a quantitative approach using experimental methods. The population used was the MI Ma'arif Suren Gede Kertek Wonosobo class with a population of 26 students. Researchers carried out data analysis using quantitative analysis methods with statistical data calculations and the formula used was the t-test formula. The results of the research showed that there was an increase in the foreign search game in experimental class students' mastery of Arabic vocabulary. This can be seen from the results of data analysis using the t-test formula which shows that t_count is greater than the existing standard value (t_table), namely 11.070> 2.27.